Aminophenol-modified gold nanoparticles kill bacteria with minimal ototoxicity - Wang, Le; Zheng, Wenfu; Zhong, Leni; Yang, Yingkun; Li, Sixiang; Li, Qizhen; Jiang, Xingyu (Chemical communications (Cambridge, England), 2022)
We report aminophenol (A)-modified gold nanoparticles (AGNPs), which have potent antibacterial effects against multidrug-resistant bacteria with a broad antibacterial spectrum. Moreover, a series of in vitro and in vivo models indicate that AGNPs are much less ototoxic than aminoglycosides. AGNPs thus have the potential to replace aminoglycosides as novel antibacterial agents for clinical applications. We report aminophenol-modified gold nanoparticles (AGNPs) that have a potent antibacterial activity and low ototoxicity. The AGNPs are promising as novel antibiotics to replace aminoglycosides.